Four aunties and a wedding [large type] - Sutanto, Jesse Q. (Thorndike Press large print core series., 2022)
"The aunties are back, fiercer than ever and ready to handle any catastrophe--even the mafia--in this delightful and hilarious sequel by Jesse Q. Sutanto, author of Dial A for Aunties. Meddy Chan has been to countless weddings, but she never imagined how her own would turn out. Now the day has arrived, and she can't wait to marry her college sweetheart, Nathan. Instead of having Ma and the aunts cater to her wedding, Meddy wants them to enjoy the day as guests. As a compromise, they find the perfect wedding vendors: a Chinese-Indonesian family-run company just like theirs. Meddy is hesitant at first, but she hits it off right away with the wedding photographer, Staphanie, who reminds Meddy of herself, down to the unfortunately misspelled name. Meddy realizes that is where their similarities end, however, when she overhears Staphanie talking about taking out a target. Horrified, Meddy can't believe Staphanie and her family aren't just like her own, they are The Family--actual mafia, and they're using Meddy's wedding as a chance to conduct shady business. Her aunties and mother won't let Meddy's wedding ceremony become a murder scene--over their dead bodies--and will do whatever it takes to save her special day, even if it means taking on the mafia"--